Arthur's loose tooth - Hoban, Lillian (New York, N.Y. : HarperTrophy, 1985)
Arthur the chimp is a little worried about losing his loose tooth, until his sister and their babysitter show him the real meaning of bravery.
420
Keywords: Teeth -- Fiction; Courage -- Fiction; Brothers and sisters -- Fiction; Babysitters -- Fiction; Chimpanzees -- Fiction